Human tumor antigens as therapeutic targets of cancer - Seon, Ben (Henry Stewart Talks, 2015)
Products of oncogenes as therapeutic targets, Differentiation antigens as therapeutic targets, Angiogenesis associated antigens as therapeutic targets, Endoglin-targeted cancer therapy